CINNAMIC ACID AND BENZAMIDE DERIVATIVES ARE POTENTIAL AS TRKA TYROSINE KINASE INHIBITORS - Laili, Nur
The receptor tyrosine kinase TRKA is a subfamily of TRK proteins that play an important role as a mediator of the development and growth process of the nervous system encoded by the NTRK1 gene. In addition to playing a role in normal cell activity, TRKA also plays a role in cancer cell activity, namely proliferation. Proliferation is the process of increasing the number of cells. NTRK1 fusion is an oncogenic activator, one of which causes an imbalance between cell division and differentiation and promotes proliferation that promotes tumor cell growth and survival. Larotrectinib and entrectinib are FDA-approved specific inhibitors for TRKA. However, mutations in TRKA residues and cancer resistance are side effects due to prolonged consumption of these specific inhibitory compounds. Therefore, the search for alternative TRKA inhibitors with minimal side effects is still being carried out. One of the efforts to find alternative inhibitors is to use inhibitors based on natural ingredients. Cinnamic acid and benzamide are natural compounds that are reported to have cancer antiproliferative bioactivity. Therefore, in this study, molecular docking of test ligands for TRKA was carried out as an initial screening to determine potential compounds as TRKA inhibitors. The test ligands used included erlotinib, artocarpine, 12 compounds derived from cinnamic acid, and 12 compounds derived from benzamide. Docking scores and test ligand interaction profiles were compared with native ligands and drug compounds for FDA-approved TRKA to support the comparison of docking results. The TRKA-ligand docking simulation was performed using the Autodock Vina program, while LigPlot+ was used to analyze the interaction. The docking simulation results obtained showed docking scores ranging from -6.7 kcal/mol to -8.6 kcal/mol. Erlotinib and artocarpine are known to have the greatest binding affinity at the active site of TRKA. However, most of the cinnamic acid and benzamide derivatives have fairly stable interactions with TRKA. This is indicated by the presence of a fairly low docking score and the involvement of one or both of the key TRKA residues, namely Glu590 and Met592. Through the evaluation of docking scores and interaction profiles that have been carried out, erlotinib, artocarpine, (2E)? N?{6?[(2,3?dihydroxypropyl)amino]hexyl}?3?(2,4,5?trihydroxyphenyl)prop?2?enamide (A9) and N?{6?[(2,3?dihydroxypropyl) amino]hexyl}?4?hydroxy?3?methoxybenzamide (B5) can be considered as potential candidates for TRKA inhibitors.